54 The Stem Cell Niche In Tendon And Ligament – Investigating Alterations With Ageing And Disease. (5th September 2014) - Lee, Katie; Williamson, Kate; Clegg, Peter; Comerford, Eithne; Canty-Laird, Elizabeth
Abstract : Introduction: Ligament and tendon are prone to degeneration through ageing and injury and current therapies are largely ineffective. The identification of a cell population within tendon with stem cell-like characteristics (Bi, 2007) holds potential for regeneration of tendon and ligament. Tendon stem cells differentiate into tenocytes (Zhang, 2010); the predominant cell type within tendon, responsible for producing extracellular matrix (ECM). The local stem cell environment (niche) is vital for stem cell maintenance and function in many tissues, and tenascin C in particular has been shown to play an important role within stem cell niches (Garcion, 2004). Tendon and ligament are composed of fascicles and interfascicular matrix (IFM) which vary considerably in composition providing definitive niches within the tissue. This study aims to characterise ECM components of the stem cell niche in equine tendon and canine ligament, which are prone to age-related degeneration. The goal of this research is to produce an in vitro environment for stem cells which mimics the stem cell niche, for treatment of tendon and ligament disease. Methods: Putative stem cells were isolated from equine superficial digital flexor tendon (SDFT) and canine anterior cruciate ligament (ACL) by low-density plating and differential adhesion to plastic and fibronectin substrates. Cells were analysed by flow cytometry using antibodies to mesenchymal stem cell markers CD90, CD73 and CD105, as well as qRT-PCR for stem cell and tenogenic markers. ECM components of the fibroblast and stem cell niche were analysed using radioisotope labelling. Cells were labelled with 14 C-labelled amino acids to specifically label newly synthesised collagenous (proline) and non-collagenous (lysine/arginine) ECM, prior to extraction of ECM. Immuno-histochemistry and histology were conducted to analyse the structure and composition of SDFT. Results: Tendon and ligament cells formed colonies after low-density plating, however only ligament cells formed colonies after differential adhesion to fibronectin. A subpopulation of tendon cells expressed CD90 in both freshly isolated cells and putative stem cells, but were CD105 and CD73 negative. Putative tendon stem cells, isolated by differential fibronectin adhesion did not exhibit increased expression of stem cell markers when compared with tenocytes. However there was a significant increase in expression of stem cell markers in putative ligament stem cells compared with ligamentocytes. Tenocytes and putative tendon stem cells (isolated by low-density plating) labelled with 14 C-labelled amino acids both displayed similar labelling profiles. Histological analysis of SDFT tissue highlighted the varied structure and composition of tendon, with tenascin C expression confined to IFM (see Figure.1 ). Conclusion: The absence of stem cell marker expression in putative stem cell populations indicates that further testing of stem cell isolation procedures is required. Published techniques for tendon stem cell isolation in humans and other mammals do not appear to be effective for isolation of equine tendon stem cells. Alternatively it is possible that the equine tendon cell population consists of a heterogenous mixture of cells at different stages of differentiation. We are currently optimising stem cell isolation techniques and conducting tri-lineage differentiation assays. Tendon stem cells in other species show tri-lineage differentiation, however it is possible that equine tendon stem cells may be restricted to tenogenic differentiation. Future experiments aim to identify ECM components of the stem cell niche by mass spectrometry and microarray comparison of tendon and ligament tissue, stem cells and fibroblasts. References: Bi et al . Nat Med. 2007;13: 1219–1227 Garcion et al . Development. 131:3423–3432 Zhang et al . Am J Sport Med. 38:2477–2486